2021
DOI: 10.1111/ppc.13006
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the relationship between smartphone addiction and job performance of healthcare employees

Abstract: To determine the smartphone addiction and employee performance levels of healthcare personnel working in a university hospital and to investigate their relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…In other words, as smartphone addiction among healthcare professionals grows, so does their performance or it might be claimed that those with high performance are less dependent on smartphones. These results are consistent with the results of previous studies in the literature (Alan, Ozen Bekar, & Güngör, 2021). In the next step, it has been determined that smartphone addiction affects job satisfaction negatively and significantly (H2 is accepted).…”
Section: Conclusion and Recommendationssupporting
confidence: 91%
See 2 more Smart Citations
“…In other words, as smartphone addiction among healthcare professionals grows, so does their performance or it might be claimed that those with high performance are less dependent on smartphones. These results are consistent with the results of previous studies in the literature (Alan, Ozen Bekar, & Güngör, 2021). In the next step, it has been determined that smartphone addiction affects job satisfaction negatively and significantly (H2 is accepted).…”
Section: Conclusion and Recommendationssupporting
confidence: 91%
“…For example, in a study conducted on healthcare employees working in a university hospital, it has been found that there is a negative relationship between smartphone addiction and performance. This has led to the conclusion that having a smartphone addiction causes employees to waste a lot of time, which has a negative impact on their performance (Alan, Ozen Bekar, & Güngör, 2021). Another study in the literature provides support for this finding.…”
Section: The Relationship Between Smartphone Addiction Employee Perfo...mentioning
confidence: 92%
See 1 more Smart Citation
“…The more addicted to smart phones, the worse the employees' job performance will be. On the contrary, some papers show that employees not relying on smartphones perform better (Alan et al, 2021). In fact, researchers have verified that overuse of smartphones increase the workload of employees, thus increasing the work pressure and breaking work-life balance .…”
Section: Job Performance Impactmentioning
confidence: 99%
“…The effect of nomophobia is thought to be related to the personality traits of individuals; however, there are not enough studies on this subject (15,29); however, studies (1,23) have been conducted to show the level of nomophobia in nursing students. In addition, there are several studies analyzing the relationship between the levels of nomophobia in varied populations and smartphone addiction and digitalization (30) with self-esteem and obesity (31), anxiety (32), and fear of missing out on developments in social environments (33) with the concepts of job performance (34). Nevertheless, while there is a study examining the relationship between the personality traits and nomophobia levels of the nurses working in a hospital (35), there is no study examining the relationship between the nomophobia levels and personality traits of nursing students in a more risky period in terms of nomophobia due to their adolescence characteristics.…”
Section: Introductionmentioning
confidence: 99%